Peningkatan Hasil Belajar Siswa Pada Pembelajaran PKn dengan Menggunakan Model Kooperatif Tipe STAD di Sekolah Dasar - Rahayu, Rahmi; Nasrul, Nasrul; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is based on the lesson of Civics that can not activate the low student learning outcomes in class V SD Negeri 04 Sungai Naniang Bukit Barisan Subdistrict of Lima Puluh Kota Regency. The purpose of this research is to describe the improvement of students' learning outcomes in the learning of Civics by applying STAD learning model on students of class V SD Negeri 04 Sungai Naniang Bukit Barisan Subdistrict, Lima Puluh Kota District. The type of research is PTK by using qualitative and quantitative approach. Student learning outcomes cycle I 67 increased to 82 in cycle II.Dengan, learning Civics by applying the model on STAD can improve learning outcomes Civics students class V SD Negeri 04 Sungai Naniang District Bukit Barisan District Lima Puluh KotaKey Word :Result study, PKn, model STAD